Hubungan Senam Hamil Terhadap Nyeri Punggung pada Trimester III di BPM Dince Safrina, SST Pekanbaru Tahun 2017 - Widya Juliarti (Institut Kesehatan dan Teknologi Al Insyirah, 2018)
ABSTRACT Pregnancy exercise is one way to strengthen the core stability of the body that will help maintain spinal health, improve balance and stability of the individual and minimize the risk of spinal trauma or falls during pregnancy and relieve back pain complaints. The purpose of this study was to see the relationship of pregnancy gymnastics to back pain in third trimester at BPM Dince Safrina, SST Pekanbaru Year 2017. This research type is analytic with cross sectional design. The population of this study is the third trimester pregnant women who visited in BPM Dince Safrina, SST Pekanbaru period January-March Year 2017 which amounted to 24 people. The sampling technique is saturated sampling. Data analysis used is univarite and bivariate analysis. Results of research conducted in April 2017 on 24 pregnant women TM III is obtained P value 0.038 <α (0,05) Odds Ratio (OR) = 10.000 (1,444-69,262). It can be concluded that there is a significant relationship between pregnancy gymnastics with back pain in third trimester pregnant women in BPM Dince Safrina, SST Year 2017 and TM III pregnant women who did not do pregnancy exercise risk 10 times experiencing back pain pregnancy dalm. It is advisable to pregnant women to be able to routinely perform pregnancy exercises as an effort to reduce back pain during pregnancy Keywords: pregnancy exercise, low back pain